Estudo piloto in vitro, da ação da naltrexona em células de queratinócitos, fibroblastos e monócitos humanos e microorganismos aeróbios: pseudomonas aeuraginosa, sthaphylococcus aureus e candida albicans - Maia, Schirley Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
There is a growing number of studies that seek new therapeutic approaches in the control of pathogenic microorganisms that affect the oral cavity. Naltrexone at substantially lower doses than recommended for the treatment of alcoholism improves and modifies the course of several diseases. The use of this substance may be useful for studies involving chronic inflammation or immune dysregulation. As numerous systemic diseases or drug side effects are reflected in the periodontium, either by direct manifestation or by modified inflammatory reaction in relation to the plaque, we believe it is relevant to evaluate the effects of this agent on the antimicrobial action. Thus, we evaluated the antimicrobial activity of the pharmacological agent on planktonic cultures of Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans, as well as the verification of the metabolic activity of cell cultures of human keratinocytes (HaCat), human fibroblasts (HFF-1) and human monocytes (THP-1) after contact with the drug. The antimicrobial analysis was performed using the broth microdilution test, according to the Clinical and Laboratory Standards Institute (CLSI), protocol M7-A9 (bacteria) and M27-A2 (Yeasts), determining the values of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MMC). Cytotoxicity assessment was performed using the MTT test, evaluating the metabolic activity of HaCaT, HFF-1 and THP-1 cells. The resistant results that the maximum concentration of 2.5 mg/mL of the drug did not result in MIC and MIC values against S. aureus, P. aeruginosa and C. albicans. The keratinocyte lineage (HaCat) obtained a maximum reduction of 7.19%, interrupted THP-1 18.4%, while fibroblasts (HFF-1) were more sensitive to the drug, showing reductions from 86.8% to 5.07%. In conclusion, Naltrexone did not exhibit antimicrobial activity on planktonic cultures of S. aureus, P. aeruginosa and C. albicans with a maximum concentration of 2.5 mg/mL, as well as the absence of cytotoxicity on keratinocytes (HaCat) and Human Monocytes (THP-1). Concentrations of 2.5 to 0.312 mg/mL exhibit metabolic toxicity on human fibroblasts (HFF-1).

É crescente o número de estudos que buscam novas abordagens terapêuticas no controle de microrganismos patogênicos que afetam a cavidade bucal. A naltrexona, um antagonista não seletivo dos receptores opioides, é usada principalmente como terapia de reabilitação para viciados em opiaceos com a finalidade de melhora da qualidade de vida destes indivíduos. Nos últimos anos, houve algumas descobertas novas e significativas sobre o uso off-label de naltrexona em doses substancialmente mais baixas do que a recomendada para este fim (LDN), modificando o curso de várias doenças, especialmente relacionados com inflamação ou desregulação imunológica. Desta forma, avaliamos a atividade antimicrobiana do agente farmacológico sobre culturas planctônicas de Staphylococcus aureus, Pseudomonas aeruginosa e Candida albicans bem como a verificação da atividade metabólica de culturas celulares de queratinócitos Humanos (HaCat), fibroblastos humanos (HFF-1) e monócitos humanos (THP-1) pós contato com o fármaco. A análise antimicrobiana foi performada pelo Teste de microdiluição em caldo, segundo Clinical and Laboratory Standards Institute (CLSI), protocolo M7-A9 (bactérias) e M27-A2 (Leveduras), determinando os valores de Concentração Inibitória Mínima (CIM) e Concentração Bactericida Mínima (CMM). A avaliação da citotoxicidade foi realizada pelo teste de MTT, avaliando atividade metabólica das células HaCaT, HFF-1 e THP-1. Os resultados demonstraram que a concentração máxima de 2,5 mg/mL do fármaco não resultou em valores de CIM e CMM frente a S. aureus, P. aeruginosa e C. albicans. A linhagem de queratinócitos (HaCat) obteve redução máxima de 7,19%, THP-1 reduziu 18,4%, enquanto fibroblastos (HFF-1) foram mais sensíveis ao fármaco, exibindo reduções de 86,8% a 5,07%. Em conclusão a Naltrexona não exibiu atividade antimicrobiana sobre culturas planctônicas de S. aureus, P. aeruginosa e C. albicans com a concentração máxima de 2,5 mg/mL bem como exibiu ausência de citotoxicidade sobre queratinócitos (HaCat) e Monócitos Humanos (THP-1). As concentrações de 2,5 a 0,312 mg/mL exibiram toxicidade metabólica sobre fibroblastos humanos (HFF-1).
In vitro pilot study of naltrexone action on keratinocytes, fibroblasts and human monocytes cells and aerobic microorganisms: pseudomonas aeuraginosa, sthaphylococcus aureus and candida albicans.
Keywords: Anti-inflamatórios; Naltrexona; Naltrexone; Anti-inflammatory agents; Microbiota; Microbiota; Receptores Toll-Like; Toll-Like receptors